1996
DOI: 10.1523/jneurosci.16-24-07859.1996
|View full text |Cite
|
Sign up to set email alerts
|

Motor Discoordination Results from Combined Gene Disruption of the NMDA Receptor NR2A and NR2C Subunits, But Not from Single Disruption of the NR2A or NR2C Subunit

Abstract: NMDA receptors consist of two distinct classes of subunits. The NR1 subunit possesses all properties of the NMDA receptor-channel complex, whereas four NR2 subunits (NR2A-2D) potentiate and differentiate NMDA receptor responses by heteromeric assemblies with NR1. The mRNAs for the five NMDA receptor subunits are expressed in the cerebellum in a distinct temporospatial manner. To study functions of the NMDA receptors in the cerebellum, we generated knockout mice deficient in either NR2A or NR2C or both of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 33 publications
12
129
3
Order By: Relevance
“…In agreement with previous reports (Ebralidze et al, 1996;Ikeda et al, 1995;Kadotani et al, 1996), NR2C nlacZ null mice do not exhibit obvious altered behaviors. However, NMDAR-EPSC peak amplitudes and charge transfer are significantly increased at autaptic synapses of cerebellar granule cells isolated from NR2C nlacZ null mice (Lu et al, 2006), consistent with previous studies performed in slices from NR2 null mice (Ebralidze et al, 1996;Takahashi et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports (Ebralidze et al, 1996;Ikeda et al, 1995;Kadotani et al, 1996), NR2C nlacZ null mice do not exhibit obvious altered behaviors. However, NMDAR-EPSC peak amplitudes and charge transfer are significantly increased at autaptic synapses of cerebellar granule cells isolated from NR2C nlacZ null mice (Lu et al, 2006), consistent with previous studies performed in slices from NR2 null mice (Ebralidze et al, 1996;Takahashi et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…An intriguing possibility is that NR1 expression is upregulated in hippocampal astrocytes by ischemia or anoxia, as previously reported (Krebs et al, 2003). Consistent with the idea that functional NR2C-containing NMDARs may be expressed in response to ischemia, cerebral vascular occlusion selectively increases NR2C mRNA expression in vulnerable areas (Small et al, 1997) and mutation of the NR2C gene reduces ischemic injury in mice (Kadotani et al, 1996). Interestingly, we observed that NR2C-nβ-gal expression is highest in CA1 and subiculum, as compared to the dentate, which coincides with regions most susceptible to global ischemic damage.…”
Section: Expression Of the Nr2c In Non-neuronal Cellssupporting
confidence: 67%
“…The GluR⑀3-KO and GluR⑀1/⑀3-KO mice were viable, grew normally, and were fertile. However, the GluR⑀1/⑀3-KO mouse showed mild impairment in motor coordination when tested on the rotating rod at high speeds (data not shown), as reported previously (Ebralidze et al, 1996;Kadotani et al, 1996).…”
Section: Production Of Glur⑀1/⑀3-ko Micesupporting
confidence: 86%
“…The most notable change emerged in the immunochemical visibility of the GluR1 subunit in the cerebellar granular layer. The order of immunohistochemical loss is grossly parallel with that in a previous electrophysiological study in which NMDA receptormediated currents are significantly reduced in granule cells lacking the GluR⑀1 or GluR⑀3 subunit, and almost absent in those lacking both subunits (Kadotani et al, 1996). The loss of the GluR1 subunit is attributable to neither transcriptional and translational downregulations nor to abnormal cellular and synaptic differentiations of granule cells.…”
Section: Discussionsupporting
confidence: 74%
“…The goal of this study was to determine how decreasing the NR2A/B ratio alters the LTD/LTP m in vitro and compare this with changes in the properties of naturally occurring plasticity in the visual cortex in vivo as a consequence of MD. We examined this question using mice with targeted disruption of one or both alleles of the NR2A gene (19). Because NR2A mutant mice do not display compensatory alterations in NR1 or NR2B subunit expression in visual cortex at the ages of interest, reducing NR2A expression effectively changes the NR2A/B ratio (10).…”
Section: Resultsmentioning
confidence: 99%